The Evolution of SAP Leadership in Insurance: A Framework for Digital Transformation - Satish Kumar Puram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the critical role of SAP Specialist Leaders in driving digital transformation within the insurance industry. The article analyzes the multifaceted responsibilities of technical leadership in implementing and optimizing SAP solutions across core insurance operations, including claims management, underwriting, and policy administration. Through a comprehensive exploration of system integration strategies, data migration methodologies, and process automation frameworks, this research highlights the intricate balance between technical excellence and business alignment. The article addresses the challenges and strategies in managing cross-functional teams, ensuring regulatory compliance, and maintaining operational continuity during large-scale SAP implementations. Furthermore, it investigates the impact of specialized leadership in enhancing customer experience, reducing operational costs, and fostering innovation within insurance organizations. This article contributes to the growing body of knowledge on technical leadership in insurance technology transformation, offering insights into effective strategies for navigating complex digital modernization initiatives.
Keywords: Digital transformation; SAP implementation; Insurance technology; Process automation; Regulatory compliance